Mesenteric cyst of Mullerian origin: a case report and review of literature - Gulzar, Saima; Tazayyen Yousaf, Rubina; Javed, Maham; Naseem, Nadia (Journal of the Pakistan Medical Association, 2024)
Mesenteric cysts are rare entities, and the Mullerian origin subtypes even rarer. They are classified on the basis of their origin and morphology. The gold standard test for diagnosis is histopathology, whereas radiological imaging provides only supportive findings. The treatment of choice is surgical excision. We present the case of a 42-year-old female who presented in the surgical emergency of Mansoorah Teaching Hospital, Lahore, on August 16, 2022, with acute abdominal pain associated with nausea and vomiting. She was initially diagnosed as a case of simple unilocular left-sided ovarian cyst based on clinical symptoms and radiological findings. However, biopsy revealed a mesenteric cyst of Mullerian origin. As mesenteric cysts are not common, therefore they becomes extremely challenging for the radiologist, pathologist, and surgeon equally, due to the difficulties encountered in their diagnosis and management. —Continue